DHAP plus filgrastim as an effective peripheral stem cell mobilization regimen for autologous stem-cell transplantation in patients with relapsed/refractory lymphoma: A single center experience. Issue 1 (February 2016) - Berber, Ilhami; Erkurt, Mehmet Ali; Kuku, Irfan; Kaya, Emin; Gozukara Bag, Harika; Nizam, Ilknur; Koroglu, Mustafa; Ozgul, Mustafa
Abstract: This study aimed to evaluate the efficiency of DHAP regimen plus filgrastim for mobilization of stem cells in patients with recurrent and/or refractory lymphoma. Thirty-four patients who took DHAP as salvage therapy prior to autologous stem cell transplantation were included. After chemotherapies, 2 cycles of DHAP plus filgrastim were administered to the patients. Stem cells from 32 patients (94%) were collected on median 11th day (8–12), and the median collected CD34 + cell dose was 9.7 × 10 6 /kg (range 3.8–41.6). DHAP plus filgrastim was found to be an effective chemotherapy regimen in mobilizing CD34 + stem cells into the peripheral.